Forest recovery after supervised and conventional logging in Ulu Muda Forest Reserve, Kedah, Malaysia - Sadeghi, Seyed Mousa (2016)
The hill dipterocarp forests (HDF) in the Ulu Muda Forest Reserve (UMFR) were logged under supervised logging (SLo) (Compartment 25A) and conventional logging (CL) (Compartment 28A) methods. Knowledge on forest recovery in terms of tree species composition, forest structure, biomass and soil of HDF after 14 and 16 years of logging is of great importance for the management of forests. A systematic sampling layout was used to assess forest recovery after supervised and conventional logging on species composition, forest structure biomass and soil physico-chemical properties. In 80 plots (50 m × 20 m) all stems with diameter at breast height (DBH) ≥ 1 cm were enumerated, measured and identified. In terms of tree species composition, forest structure, biomass and soil, data were compared between Compartments (SLo & CL) or with Pre-Felling (Pre-F) data in order to find the forest recovery after SLo and CL. The soil samples in 27 sub-plots were collected. The chemical and physical analyses of soil were performed. The soil fertility index (SFI)and soil evaluation factors (SEF) were calculated to compare the differences of soil recovery between SLo and CL sites. In term of species composition 501 species belonging to 208 genera and 71 families were recorded. The tree species composition of the study site contributed to 17.7%, 40.6% and 71.0% of total tree species, genera and families found in Peninsular Malaysia; of these 79 are endemic species including eight rare species and one very rare species. Five new records for Kedah; Diospyros apiculata, Diospyros argentea, Macaranga recurvata, Macaranga constricta and Cryptocarya bracteolata were found in the study site. Euphorbiaceae was the most diverse family, followed by Lauraceae, Annonaceae, Rubiaceae and Meliaceae. In term of species importance value index (IVI) Shorea macroptera (26.0) and Ochanostachys amentacea (26.7) were the two most important species in the SLo and CL sites, respectively. In term of family importance value (FIV) Euphorbiaceae was the most important family in the SLo (70.2) and CL (78.2) sites. The forests after SLo and CL are still rich in biodiversity this is shown by Margalef index of SLo and CL sites were 49.58 and 33.38,respectively. Shannon-Weiner, Simpson and Fisher indices for SLo and CL sites were 5.44 and 4.89, 151.4 and 84.5, 119.7 and 70.36, respectively. Smith and Wilson evenness values of SLo and CL sites were 0.46 and 0.38, respectively. The difference between diversity indices of SLo and CL sites were significant at 5% level. Sorensen and Jaccard similarity indices between SLo and CL sites were 0.60 and 0.43, respectively. Considering the recovery, in term of species composition the SLo site recovered more than CL site which was 63.1%.In term of forest structure for trees with DBH > 5 cm, the mean values of tree density of SLo (636.6 stem ha-1) and CL (620.6 stem ha-1) sites were significantly higher than Pre-Felling (Pre-F) data (448.2 stem ha-1) (Sig. = 0.000 in both sites).Distribution of tree density based on tree groups (DBH ≥ 5 cm) showed that small pole, big pole, and small tree groups recovered up to or more than Pre-F data. The average basal area of trees with DBH > 15 cm, from Pre-Felling data (24.7 m2 ha-1)was higher than the values of inventory data in the SLo (21.1 m2 ha-1) and CL (17.2 m2 ha-1) sites (Sig. = 0.03 and Sig. = 0.00 for SLo and CL sites, respectively). With respect to tree volume for trees with DBH > 15 cm, the inventory data of SLo (148.0 m3 ha-1) and CL (123.0 m3 ha-1) sites were significantly lower than Pre-Felling data(205.7 m3 ha-1) (Sig. = 0.001 and 0.000 for SLo and CL sites,respectively). Trees with DBH 15-45 cm recovered in term of tree density, basal area and volume when compared with Pre-Felling data. The mean values of total biomass and total carbon for tree (DBH ≥ 1cm) in the SLo site were 326.7 ton ha-1 and 163.4 ton ha-1,respectively but were non-significantly higher than those values in the CL site (275.2 ton ha-1 and 137.6 ton ha-1, respectively) (Sig. = 0.3). Forest recovery of tree species diversity, basal area, tree volume and total biomass in terms of percentage in the SLo site was higher than the values of CL site by 14.3%, 22.7%, 20.3% and 21.8%,respectively. However, in terms of tree density, basal area and volume for trees with DBH > 15 cm, a big loss value (Pre-F value minus value from inventory data) was found when compared to the overall inventory data with Pre-Felling data. The loss value for tree density, basal area, and volume of SLo site were 48.7%, 14.6%, 28.1% and that of CL site were 52.5%, 30.4% and 40.2%, respectively. The forest in both sites has five strata. The soil evaluation factor (SEF) of SLo site (9.2±4.1) was nonsignificantly(4.3%) smaller than that value of CL (9.6±3.6) site (Sig = 0.8). The soil fertility index (SFI) of CL site was non-significantly higher than SLo site (Sig. = 0.4). Results showed that logged forest recovered in terms of species composition,diversity and forest structure for trees with DBH 1-45 cm, but not for trees of DBH >45 cm. In terms of biomass the logged forest to some extent recovered but 14 and 16 years after logging were not sufficient for forest to recover up to its fully capacity.For soil recovery, it needs more than 14 and 16 years after logging. The result showed that 3-ha and 5-ha sampling size in the both study sites were not enough to capture the plant diversity of study sites. Hence, further study was suggested to find the optimum plant diversity sampling size. In order to improve accuracy of biomass estimation in logged-over HDF it was recommended to do future study for generating biomass equation. Results of this study could be useful for both decision makers and foresters to improve tropical rainforest management.